KOSOVO AND COLONIAL DISCOURSE (Heritage, 2024)
In intellectual debates, as well as in the field of political confrontation, in Serbia, for years, they have been on the side of the extreme opposing population, which we can collectively call the national discourse. These two discourses also determine the reception of the current Kosovo problem. The national discourse, although present in numerous retouches, from the left to the extreme right, represents a critical confrontation with theoretical "principles" and political "solutions", regardless of their origin. Collinial discourse, on the other hand, implies the acceptance of both intellectual matrices and political platforms, which are established in international cultural or political centers. In this sense, the colonial discourse is articulated as an expert discourse. In other words, here the immediate political strategy of national security, when it comes to Kosovo, is justified not by the current power relations, but by the apology of those parameters that have turned out to be insurmountable "red lines" of powerful Western countries and international organizations in which they have the most influence. One of the concepts that gained importance in the colonial discourse is the concept of open dialogue. In this sense, collinear discourse actually makes critical discourse impossible, that is, the questioning and critical reception of ideologically or politically based solutions to the Kosovo issue.
Keywords: Intellectuals, Colonial discourse, National discourse, |Nationalism, Criticism, Kosovo issue